Biotechnology : (Wiley-VCH, 2000)
Biotransformations have developed into an important tool of organic synthesis and most synthetic sequences will benefit from the use of a biotransformation step. This volume completes the collection of biotransformations presented in the Biotechnology series. Volumes 8 a and b provide a comprehensive guide to the established and emerging uses of enzymes, each chapter is devoted to a single class of transformation.